2022
DOI: 10.1111/andr.13215
|View full text |Cite
|
Sign up to set email alerts
|

Expression of membrane fusion proteins in spermatozoa and total fertilisation failure during in vitro fertilisation

Abstract: Background: Couples increasingly experience infertility and seek help from assisted reproductive techniques to become pregnant. However, 5%-15% of the couples that are selected for in vitro fertilisation (IVF) experience a total fertilisation failure (TFF), where no zygotes develop despite oocytes and semen parameters appear to be normal.We hypothesise that TFF during IVF could be related to improper membrane fusion of gametes.Objective: To investigate the membrane integrity and fusion proteins in spermatozoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…Bjerregaard and colleagues indicated that a strong Syncytin 1 expression was present in the sperm acrosome or the equatorial segment and a weak staining pattern was observed in the midpiece and tail regions [ 53 ]. Recently, a similar expression pattern was also reported by Enoiu and colleagues with visible diffusion to the entire head in all sperm samples [ 54 ]. While the expression of Syncytin 1 in the acrosome, equatorial segment, midpiece, and tail regions of sperm is similar to the previous studies, here, we demonstrated that there is a more complex expression profile of Syncytin 1 suggesting a heterogeneity in human spermatozoa.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Bjerregaard and colleagues indicated that a strong Syncytin 1 expression was present in the sperm acrosome or the equatorial segment and a weak staining pattern was observed in the midpiece and tail regions [ 53 ]. Recently, a similar expression pattern was also reported by Enoiu and colleagues with visible diffusion to the entire head in all sperm samples [ 54 ]. While the expression of Syncytin 1 in the acrosome, equatorial segment, midpiece, and tail regions of sperm is similar to the previous studies, here, we demonstrated that there is a more complex expression profile of Syncytin 1 suggesting a heterogeneity in human spermatozoa.…”
Section: Discussionsupporting
confidence: 82%
“…The decreased expression of Syncytin 1 and its receptor may cause failure by negatively affecting fertilization and embryo growth and can be used as important biomarker molecules in the development of new strategies in IVF treatments. A recent study by Enoiu and colleagues investigated the fusion proteins including Syncytin 1 in spermatozoa from men in couples experiencing total fertilization failure during IVF [ 54 ]. However, the study reported that there were not any significant changes in the expression of Syncytin 1 between the total fertilization failure and control groups [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IZUMO1 deletion blocks gamete fusion ( Inoue et al, 2005 ), and JUNO was identified as the IZUMO1 receptor in the oocyte ( Bianchi et al, 2014 ). Evidence from infertile patients suggests that these proteins play a role during human fertilization ( Clark and Naz, 2013 ; Yu et al, 2018 ; Enoiu et al, 2022 ). The IZUMO1–JUNO interaction mediates gamete binding ( Matsumura et al, 2021 ) in a species-specific manner ( Bianchi and Wright, 2015 ).…”
Section: Introductionmentioning
confidence: 99%